Fontes versus fatos. estudo sobre assessoria de imprensa e a construção de narrativas na Fórmula 1 - Xavier, Victoria Carneiro (My University, 2025)
This study is dedicated to discussing the role of the Press Office in the counterpoint between sources and facts in the construction of narratives in Formula 1. The research aims to: discuss the concepts of sources and facts in Journalism; present the characteristics of press offices, particularly related to the construction of narratives; relate Journalism and Press Office to Formula 1; and report and discuss the analyzed case: a controversy involving team principal Christian Horner and the stance of press offices in Formula 1. The research is exploratory, with a qualitative approach, and adopts the methodological strategies of Cartography of Knowledge and Rhizomatic Matrices, as proposed by Baptista (2014). The theoretical framework addresses topics such as Journalism, Sources, Facts, and the Construction of Narratives in the Press Office, and is based on authors such as Schmitz (2011), Kovach and Rosenstiel (2004), Carvalho and Ferreira (2015), Pena (2013), Motta (2005), Sponholz (2009), Traquina (2001), and Dalmaso (2002). In addition, 14 statements from Formula 1 spokespersons were collected regarding the inappropriate behavior investigation involving the Red Bull Racing team principal, Christian Horner. In order to understand how the sources were guided to take a stance on the case, the press offices of the teams were contacted. The research analyzed the statements and stances to identify how the narratives around the episode were constructed. The results indicate that the press offices adopted two main approaches, according to their interests: isolating or amplifying the fact. [resumo fornecido pelo autor]
O presente trabalho dedica-se a discutir o papel da Assessoria de Imprensa em relação ao contraponto fontes e fatos, na construção de narrativas na Fórmula 1. Os objetivos da pesquisa são: discutir os conceitos fontes e fatos no Jornalismo; apresentar as características da Assessoria de Imprensa, especialmente relacionadas à construção de narrativas; relacionar Jornalismo e Assessoria de Imprensa à Fórmula 1; e relatar e discutir o caso analisado: polêmica envolvendo o chefe de equipe Christian Horner e a posição das assessorias de imprensa na Fórmula 1. A pesquisa é exploratória, de orientação qualitativa, e adota as estratégias metodológicas Cartografia dos Saberes e Matrizes Rizomáticas, conforme Baptista (2014). O referencial teórico abrange temas como Jornalismo, Fontes, Fatos e a Construção de Narrativas na Assessoria de Imprensa, e baseia-se em autores como Schmitz (2011), Kovach e Rosenstiel (2004), Carvalho e Ferreira (2015), Pena (2013), Motta (2005), Sponholz (2009), Traquina (2001) e Dalmaso (2002). Além disso, foram coletadas 14 declarações de porta-vozes da Fórmula 1 sobre a investigação por conduta imprópria envolvendo o chefe de equipe da Red Bull Racing, Christian Horner. Para compreender como as fontes foram orientadas a se posicionar sobre o caso, as assessorias de imprensa das equipes foram contatadas. A pesquisa analisou as declarações e os posicionamentos para identificar como ocorreu a construção de narrativas em torno do episódio. Os resultados indicam que as assessorias adotaram duas abordagens principais, conforme seus interesses: isolar ou ampliar o fato. [resumo fornecido pelo autor]
Keywords: Jornalismo; Assessores de imprensa